2022
DOI: 10.3389/fgene.2022.918584
|View full text |Cite
|
Sign up to set email alerts
|

Causal Effect of Age at Menarche on the Risk for Depression: Results From a Two-Sample Multivariable Mendelian Randomization Study

Abstract: A fair number of epidemiological studies suggest that age at menarche (AAM) is associated with depression, but the reported effect sizes are small, and there is evidence of residual confounding. Moreover, previous Mendelian randomization (MR) studies to avoid inferential problems inherent to epidemiological studies have provided mixed findings. To clarify the causal relationship between age at menarche and broadly defined depression risk, we used 360 genome-wide significantly AAM-related single-nucleotide poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 92 publications
3
16
0
Order By: Relevance
“…Thus, adverse outcomes regarding mental health conferred by the genotype underlying pubertal timing might be counterbalanced by advantageous effects related to the same set of genes and their individual allelic architecture in males but not in females. This would explain the findings of the present study as well as the observation of adverse effects of earlier pubertal timing in girls on the mental health phenotype (Hirtz et al, 2022).…”
Section: Closely Related But Yet Distinct -Pubertal Timing In Girls A...supporting
confidence: 75%
See 1 more Smart Citation
“…Thus, adverse outcomes regarding mental health conferred by the genotype underlying pubertal timing might be counterbalanced by advantageous effects related to the same set of genes and their individual allelic architecture in males but not in females. This would explain the findings of the present study as well as the observation of adverse effects of earlier pubertal timing in girls on the mental health phenotype (Hirtz et al, 2022).…”
Section: Closely Related But Yet Distinct -Pubertal Timing In Girls A...supporting
confidence: 75%
“…However, for valid conclusions of the MR, the genetic architecture of depression should not change throughout the life course. As previously discussed in more detail (Hirtz et al, 2022), a recent genome-wide association meta-analysis showed that the genetic architecture of . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Male Pubertal Timing and Mddmentioning
confidence: 74%
“…Years of schooling were converted and standardized, where each unit represented 4.2 years of schooling (1 standard deviation [SD] = 4.2 years). Based on published MR studies ( 17 , 18 ), a total of 268 single nucleotide polymorphisms (SNPs) were selected in our study for MR analysis ( Supplementary Table 2 ). According to previous studies, these SNPs accounted for 12% of the variation in EA among individuals ( 16 ).…”
Section: Methodsmentioning
confidence: 99%
“…Mental health has been linked to certain reproductive behaviors (RB) and socioeconomic status (SES) (7) (8) (9).Postpartum depression, being a mental disorder associated with childbirth, is susceptible to being in uenced by women's reproductive behaviors. To date, various studies have found that early age at menarche and menopause, as well as early age at rst intercourse, are linked with an increased risk of depression (10) (11) (12).…”
Section: Introductionmentioning
confidence: 99%